1994
DOI: 10.1002/chin.199449235
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Convenient Synthesis of Optically Pure (2R,3R)‐2,3‐Epoxysuccinyl‐ Dipeptides.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…30 We noted that the basic arginine residues of the CPP in the probe can bind ionized TFA in H 2 O, possibly resulting in a difficult evaporation of TFA during freeze-drying and thus leading to a persistent pH decline, which probably opened the oxirane ring of the probe. 30 Therefore, a mixture containing only TIS (2%) and TFA (anhydrous, 98%) rather than a commonly used mixture consisting of TFA/H 2 O/TIS (95:2.5:2.5) was employed as the cleavage cocktail in the solid-phase synthesis to avoid the ionization of TFA. After the cleavage, the crude products were neutralized to pH 7 with several drops of ethanediamine.…”
Section: ■ Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…30 We noted that the basic arginine residues of the CPP in the probe can bind ionized TFA in H 2 O, possibly resulting in a difficult evaporation of TFA during freeze-drying and thus leading to a persistent pH decline, which probably opened the oxirane ring of the probe. 30 Therefore, a mixture containing only TIS (2%) and TFA (anhydrous, 98%) rather than a commonly used mixture consisting of TFA/H 2 O/TIS (95:2.5:2.5) was employed as the cleavage cocktail in the solid-phase synthesis to avoid the ionization of TFA. After the cleavage, the crude products were neutralized to pH 7 with several drops of ethanediamine.…”
Section: ■ Resultsmentioning
confidence: 93%
“…During the synthesis of the probe, we found that if a mixture of TFA with H 2 O was used in the cleavage of the probe from the solid support or during HPLC separation, the probe was unstable during freeze-drying, possibly owing to the occurrence of nucleophilic oxirane ring opening . We noted that the basic arginine residues of the CPP in the probe can bind ionized TFA in H 2 O, possibly resulting in a difficult evaporation of TFA during freeze-drying and thus leading to a persistent pH decline, which probably opened the oxirane ring of the probe . Therefore, a mixture containing only TIS (2%) and TFA (anhydrous, 98%) rather than a commonly used mixture consisting of TFA/H 2 O/TIS (95:2.5:2.5) was employed as the cleavage cocktail in the solid-phase synthesis to avoid the ionization of TFA.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…(2R,3R)-Ethyl 3-(4-(3-Bromoanilino)quinazolin-6-ylcarbamoyl)oxirane-2-carboxylate (4). Method A. Dichloromethylene dimethyliminium chloride (356 mg, 2.19 mmol) was added to a stirred solution of (2R,3R)-2,3-epoxysuccinic acid monoethyl ester 17 38 (350 mg, 2.19 mmol) in anhydrous CH 2 Cl 2 (10 mL). After the reactants were stirred for 1 h with ice-cooling, 6amino-4-(3-bromoanilino)quinazoline 3 (458 mg, 1.46 mmol) and NaHCO 3 (613 mg, 7.3 mmol) were added, and the suspension was stirred for 1 h at 0 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Carboxylic acids 20 − 24 are commercially available, while 17 − 19 , 25 , 26 , and the ester 27 were prepared as shown in Schemes and . The (2 R ,3 R )-epoxy diester 32 was partially hydrolyzed to the desired (2 R ,3 R )-monoethyl ester 17 or selectively monoreduced to the hydroxyl ester 33 . Mesylation of the alcohol 33 and substitution with piperidine gave the epoxy ester 34 , which was hydrolyzed to afford the desired carboxylate 19 .…”
Section: Chemistrymentioning
confidence: 99%